Absorbing boundary condition for scalar-wave propagation problems in infinite media based on a root-finding algorithm - Lee, Jin Ho; Tassoulas, John L. (Computer methods in applied mechanics and engineering, 2018)
In this study, we propose a new approach for development of absorbing boundary conditions for scalar-wave propagation problems in infinite media based on a root-finding algorithm for the solution of the exact wave dispersion relation. We select the Newton–Raphson method as the root-finding algorithm in the present study and assess the accuracy of the newly developed boundary condition by estimating its reflection coefficient. Furthermore, we evaluate and verify the stability of the boundary condition. We apply our development to various scalar-wave propagation problems and demonstrate that the proposed approach leads to accurate and stable computations. •New boundary conditions are proposed for unbounded domains to absorb scalar waves.•A root-finding algorithm for the solution of exact dispersion relation is utilized.•In the present study, we select the Newton–Raphson method as the algorithm.•We assess the accuracy of the new boundary condition and verify its stability.•We demonstrate that the proposed approach leads to accurate and stable computations.